Correlation between the direction of prompt neutrons and fragments in the fission process as a tool for studying rotation effect - Berikov, D; Ahmadov, Gadir; Kopatch, Yuri; Nuruyev, Sabuhi; Mendibayev, Kairat; Ahmadov, Farid (Eurasian Journal of Physics and Functional Materials, 2026)
This paper investigates the possibility of restoring the trajectory of fission fragments using thick targets that are opaque to the fragments, by analyzing the angular distribution of prompt neutrons. Employing thick targets in experimental studies with low-intensity neutron beams accelerate the accumulation of statistics, thereby facilitating the study of subtle effects, such as the rotation (ROT) effect which sheds light on the deformation and rotational behavior of fission fragments. The paper details the experimental techniques used, presents the results of neutron yield measurements from the fission of 235U with cold and “warm” (60 meV) neutrons in the range of angles from 0 to 360 degrees (in 22.5 degrees increments). The analysis of these is also presented. Recommended Citation Berikov, D.; Ahmadov, G.; Kopatch, Yu.; Nuruyev, S.; Mendibayev, K.; and Ahmadov, F. (2024) "Correlation between the direction of prompt neutrons and fragments in the fission process as a tool for studying rotation effect," Eurasian Journal of Physics and Functional Materials: Vol. 8: No. 2, Article 5. DOI: https://doi.org/10.69912/2616-8537.1191